Foreign Relations with The Arabs Before Islam: (Embassy model) - Hazim Jasim, Wathiqa (Al-Adab Journal, 2021)
The issue of foreign relations between Arab tribes, especially the embassy, ​​is one of the most important issues, as it sheds light on the nature of political relations between Arab tribes, which were in conflict with each other on the one hand. And between it and the neighboring countries on the other hand before Islam. Arab tribes' resort to the diplomatic method to limit these disputes by peaceful means, by sending their ambassadors. In order not to develop these conflicts and affect in one way or another the nature of the relations between them. This is an aspect of influencing and being affected by those embassies, and the ambassador may be sent for economic purposes in order to conclude trade agreements between the Arab tribes to secure their safety.To assume the position of ambassador, he must fulfill several conditions, including: To be distinguished by wisdom, statesmanship, tact in speech, integrity of language, and to have a method of persuading opponents by using diplomatic methods and establishing peace bonds between the two conflicting parties; The last to take over the embassy from the Quraish before Islam was Omar ibn al-Khattab.